New directions in learning, teaching and assessment for phonetics - Michael Ashby (Estudios de Fonética Experimental)
This paper gives an account of a series of grant-funded initiatives at UCL over the last four years, developing innovations in the teaching, learning and assessment of phonetics within a university context. The first project set out to investigate the value of computers and other IT equipment (such as wireless microphones) applied within small-group advanced practical training, and demonstrated considerable benefits in flexibility, as well as suggesting new perspectives on the interface between phonetics teaching and research. Next, the PHONLINE project is outlined, which we believe to be the first comprehensive attempt to develop an online distance course making available most of the elements of established on-campus phonetic training within a VLE. This project showed how the interactive online mode of presentation encourages the inclusion of research findings even in a foundation-level syllabus and led to further work, now in progress, aiming to develop opportunities for greater interactivity and particularly to explore the use of further audio tools (such as VoIP), both within and in parallel to the VLE, to achieve this. In a final section, we point out that developments in teaching and learning need to be matched by corresponding innovation in assessment, and report a project concerned with providing a background for the development of meaningful and efficient assessments in phonetics, with a survey of assessment types against a conceptual framework from educational theory.